Campaign hots up as Pengkalan Kubor voters set to pick new rep tomorrow - Borneo Post, (KK) (BorneoPost Online, 2014)
TUMPAT: Voters in the Pengkalan Kubor state constituency have most probably decided on the choice of their next assemblyman from among the three candidates contesting the byelection, polling for which is on Thursday.